Стимуляція синтезу інсуліну в бета-клітинах підшлункової залози у інтактних щурів і щурів з діабетом при хронічному введенні аргінін-вазопресину - Абрамов, Андрій Володимирович; Abramov, A. V. (My University, 2000)
Investigations on the intact and diabetic rats show us that chronical administration of [Arg8]-vasopressin for ten days (intracerebroventricular 24 pg or intraperitoneal 240 ng every day) leds to the increasing of insulin's level in beta-cells of the pancreas in normoglycemic rats to 6, % ± 0,2 % in comparison with the control group, and in hyperglycemic diabetic rats to 25,9 % ± 0,6 % at the intracerebroventricular infusions, and to 15,9 % ± 0,8 % at the intraperitoneal injections. The administrations of vasopressin in animals with experimental diabetes mellitus leds to the devreasing of glycemia's level in average to 37 %, but do not have an influence on the destruction of Lanhergan's islets. Probably an insulin-stimulating effect of intracerebroventricular infusions of vasopressin is connected with the modulation of functional activity of hypothalamic centres of food behaviour and dorsal motor nucleus of vagal nerve and in peripherial injections vasopressin directly stimulates insulin synthesis.
Chronical administrations of arginine-vasopressin stimulate insulin.s synthesis in beta-cells of pancreas in intact and diabetic rats